Influência de fatores ambientais na composição química do óleo essencial e nos teores de substâncias fenólicas das folhas de Syzygium jambos L. Alston - Myrtaceae - Rezende, Wilma Pereira de (2012)
The species Syzygium jambos L. Alston - Myrtaceae, popularly known as yellow jambo, is an Asian tree, predominant in tropical and subtropical regions. Studies show the presence of phenolic compounds, flavonoids, tannins and essential oil. In addition to describing an antioxidant and antimicrobial activity in its hydroethanolic extract, more than in some other species so far considered as very promising. This study was aimed at evaluating the influence of environmental factors such as seasonality, temperature, rain precipitation, soil and leaf mineral nutrients on the essential oil composition and levels of phenolic compounds extracted from the leaves of Syzygium jambos. Samples were collected in two distinct regions: in the northeast and southeast of the state of Goiás, and in the cities Nova America and Rio Verde in dry periods in July and in rainy periods in January, both in 2011. The essential oil was extracted by hydrodistillation in a Clevenger device, modified and submitted to analysis by gas chromatography, attached to mass spectrometry (CG/EM). The dosage of the phenol compounds were made by spectrophotometry. The levels of soil and leaves nutrients were analyzed by spectrophotometric methods and atomic absorption. The data were submitted to Pearson correlation analysis, multiple regression and hierarchical clustering. The results showed that environmental variables on the location had greater influence on the chemical variability of essential oils and phenolic compounds obtained from the leaves of S. jambos. Its content and composition also showed different data according to the time of harvest.